Analisis Penerapan Manajemen Risiko pada Lelang Surat Utang Negara (SUN) - Sandi Simatupang, Michael Harry; Elisa Susanti (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to understand the implementation of risk management in the Government Securities (SUN) auction process by the Directorate General of Financing and Risk Management (DJPPR) of the Ministry of Finance of the Republic of Indonesia. The research method used is a descriptive qualitative approach with triangulation techniques in the form of in-depth interviews and documentation studies. The results indicate that DJPPR has implemented comprehensive risk management based on the COSO ERM framework (2004), starting from establishing the internal environment, setting objectives, assessing and controlling risks, to controlling activities, communication, and monitoring. The conclusion of this study is that DJPPR has succeeded in establishing a comprehensive and responsive risk management system that supports fiscal stability and increases investor confidence in the government securities market.   Keywords: Risk Management, SUN Auction, DJPPR, COSO ERM, Fiscal Stability